A Bio inspired optimization with Reliable QoS Routing through Efficient Packet Transmission in Mobile ad-hoc Network. (June 2022) - Venkata Subbaiah, C.; Govinda, K.
Abstract: A collection of mobile devices is defined as a Mobile Ad-hoc Network (MANET). Without any prior management these devices can communicate and synchronize with one another. The state of the concerned channel determines how much life energy can be increased. It also extends the node's lifetime while it waits for the control messages to be completed. The nodes' lifespan and packet flow quality are harmed in the current system due to unanticipated energy conservation strategies. It causes post-network collapse due to an energy throughput trade off. This failure causes an increase in overhead and a decrease in Time-to-Live (TTL). In addition to proposing a novel performance modeling in Volunteered Computing MANET and tactile internet, this paper discusses an effective buffer management mechanism. The best execution the nodes can achieve with fractional data is depicted for utilities in general. A switch state promoting Optimized mutual MAC (OMAC) process was presented in this study for node conserving energy and the optimal utilization of accessible nodes before their resource drain to link the space between network efficiency conservation based on minimal overhead. As proof of the proposed solution, simulation results are provided. Compared the simulation outcomes with the existing system using the parameters like latency, quantity, node availability & energy consumption.